2015
DOI: 10.1038/ismej.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal patterns of diversity and functional traits of metabolically active microorganisms in stream biofilms

Abstract: Resources structure ecological communities and potentially link biodiversity to energy flow. It is commonly believed that functional traits (generalists versus specialists) involved in the exploitation of resources depend on resource availability and environmental fluctuations. The longitudinal nature of stream ecosystems provides changing resources to stream biota with yet unknown effects on microbial functional traits and community structure. We investigated the impact of autochthonous (algal extract) and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 51 publications
4
37
0
Order By: Relevance
“…The study, which analysed 14 biofilms grown in laboratory-scale bioreactors mimicking the hyporheic zone, showed that the likelihood of sustaining such enzymatic multifunctionality decreases with decreasing microbial diversity, indicative of a low level of redundancy. Another study reconstructed artificial metagenomes to derive 140 orthologues related to carbohydrate and amino acid metabolism in benthic biofilms from alpine streams 81 . Analysing the association between inferred metabolic multifunctionality and bacterial diversity revealed a high degree of metabolic redundancy, which means that the biofilm microbiome is able to metabolize a wide range of DOM compounds in the streamwater, regardless of community composition.…”
Section: Diversity and Functionmentioning
confidence: 99%
“…The study, which analysed 14 biofilms grown in laboratory-scale bioreactors mimicking the hyporheic zone, showed that the likelihood of sustaining such enzymatic multifunctionality decreases with decreasing microbial diversity, indicative of a low level of redundancy. Another study reconstructed artificial metagenomes to derive 140 orthologues related to carbohydrate and amino acid metabolism in benthic biofilms from alpine streams 81 . Analysing the association between inferred metabolic multifunctionality and bacterial diversity revealed a high degree of metabolic redundancy, which means that the biofilm microbiome is able to metabolize a wide range of DOM compounds in the streamwater, regardless of community composition.…”
Section: Diversity and Functionmentioning
confidence: 99%
“…The few recent studies considering such land-water linkages have shown not only that this connectivity with the terrestrial environment may influence aquatic microbial communities by providing nutrients and dissolved organic matter of different quality (Besemer et al, 2013;Berggren and del Giorgio, 2015;Ruiz-González et al, 2015a;Wilhelm et al, 2015), but also that the immigration of microbes from the surrounding catchment can largely explain the local composition of the receiving community. For example, terrestrial runoff causes the advection of high numbers of bacterial taxa to aquatic bodies, and consequently the systems most tightly connected to the landscape will be more strongly influenced by this transport of terrestrial bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Finger et al, 2012;Majone et al, 2016), determines the habitat suitability of numerous aquatic organisms (e.g. Short and Ward, 1980;Hari et al, 2006;Wilhelm et al, 2015;Padilla et al, 2015) and even plays a noticeable role in the global emission of carbon dioxide into the atmosphere (Butman and Raymond, 2011;Raymond et al, 2013).…”
Section: Introductionmentioning
confidence: 99%